Gains–loss asymmetry of jobs, income, and risk-taking behaviors - Nguyen, Holly (Criminology, 2024)
Despite extensive theorizing on the employment-crime link, little discussion has taken place on the mechanisms through which job gains and losses affect behavior. We draw on prospect theory and the loss aversion principle, which suggests people are more sensitive to losses than gains, to assess how individuals contend with transitions in employment and income. Using fixed-effects and asymmetrical fixed-effects models, we analyze 36 months of retrospective information for a sample of incarcerated males collected as part of the Second Nebraska Inmate Study. First, we assess whether job losses are more likely than job gains to generate financial stress and find support for the loss aversion principle. Second, we explore how people might compensate for changes in job and income status by engaging in risk-taking behaviors (illegal earnings, gun carrying, and offending versatility). We find the positive relationship between job and income loss on the probability of reporting illegal earnings and crime versatility is stronger than the negative relationship between job and income gain and these behaviors. Financial stress, however, does not attenuate the relationship between losses and risk-taking behaviors. We discuss the implications for theory and policy.